2009
DOI: 10.1603/029.102.0224
|View full text |Cite
|
Sign up to set email alerts
|

Potential New Insecticides for the Control of Western Flower Thrips (Thysanoptera: Thripidae) on Sweet Pepper, Tomato, and Lettuce

Abstract: New pesticides are required to maintain effective resistance management strategies for control of western flower thrips, Frankliniella occidentalis (Pergande) (Thysanoptera: Thripidae). We tested the efficacy of acetamiprid, and thiamethoxam, two neonicotinoids that represent a newer class of insecticides for the control of thrips. We also tested chlorfenapyr, a pyrrol compound, and a lower than registered rate of the biopesticide spinosad. Laboratory bioassays were used to predict the relative efficacy of ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 19 publications
3
24
0
Order By: Relevance
“…(2 There were minor variations in the efficacy of various insecticides from 2011 to 2012, but acetamiprid could not control F. occidentalis in both years. Acetamiprid, which was used as a grower standard in the current studies, effectively controlled F. occidentalis in laboratory and greenhouse studies on lettuce, pepper, and tomato in an earlier study by Broughton and Herron [18]. Results indicate possible resistance to acetamiprid and suggest a need for rotating insecticides from different modes of action groups both as a means of resistance management and to achieve effective control.…”
Section: Studymentioning
confidence: 62%
“…(2 There were minor variations in the efficacy of various insecticides from 2011 to 2012, but acetamiprid could not control F. occidentalis in both years. Acetamiprid, which was used as a grower standard in the current studies, effectively controlled F. occidentalis in laboratory and greenhouse studies on lettuce, pepper, and tomato in an earlier study by Broughton and Herron [18]. Results indicate possible resistance to acetamiprid and suggest a need for rotating insecticides from different modes of action groups both as a means of resistance management and to achieve effective control.…”
Section: Studymentioning
confidence: 62%
“…Spinosad acts either upon contact or ingestion (Cloyd 2009). No other insecticide class provides this level of control (Funderburk et al 2000;Broughton & Herron 2009). The unique mode of action of spinosyn-based insecticides and their translaminar properties have made them highly effective against WFT (Demirozer et al 2012).…”
Section: Biology and Problems Concerning Frankliniella Occidentalismentioning
confidence: 99%
“…Neonicotinoids, which have been used since the 1990's to manage various types of other sucking insect pests, have recently received attention for a potential role in western flower thrips management. In experimental trials in Australia, Broughton and Herron (2009) found that two neonicotinoids, acetamiprid and thiamethoxam, were as effective as spinosad against larvae and adults of western flower thrips in pepper and lettuce. However, none of the tested insecticides, including spinosad, were effective in reducing the abundance of western flower thrips adults in tomato.…”
Section: Insecticide Use and Insecticide Resistancementioning
confidence: 99%
“…Likewise, the pyrrrol chlorfenapyr is registered for greenhouse ornamental and vegetables in the USA, but is approved for use in other situations globally. It has shown efficacy comparable to spinosad in greenhouse trials conducted in Australia (Broughton & Herron, 2009). Both pyridalyl and chlorfenapyr have translaminar properties.…”
Section: Insecticide Use and Insecticide Resistancementioning
confidence: 99%